Copper oxide nanoparticles aggravate airway inflammation and mucus production in asthmatic mice via MAPK signaling. Issue 4 (20th April 2016) - Park, Ji-Won; Lee, In-Chul; Shin, Na-Rae; Jeon, Chan-Mi; Kwon, Ok-Kyoung; Ko, Je-Won; Kim, Jong-Choon; Oh, Sei-Ryang; Shin, In-Sik; Ahn, Kyung-Seop
Abstract: Copper oxide nanoparticles (CuONPs), metal oxide nanoparticles were used in multiple applications including wood preservation, antimicrobial textiles, catalysts for carbon monoxide oxidation and heat transfer fluid in machines. We investigated the effects of CuONPs on the respiratory system in Balb/c mice. In addition, to investigate the effects of CuONPs on asthma development, we used a murine model of ovalbumin (OVA)-induced asthma. CuONPs markedly increased airway hyper-responsiveness (AHR), inflammatory cell counts, proinflammatory cytokines and reactive oxygen species (ROS). CuONPs induced airway inflammation and mucus secretion with increases in phosphorylation of the MAPKs (Erk, JNK and p38). In the OVA-induced asthma model, CuONPs aggravated the increased AHR, inflammatory cell count, proinflammatory cytokines, ROS and immunoglobulin E induced by OVA exposure. In addition, CuONPs markedly increased inflammatory cell infiltration into the lung and mucus secretions, and MAPK phosphorylation was elevated compared to OVA-induced asthmatic mice. Taken together, CuONPs exhibited toxicity on the respiratory system, which was associated with the MAPK phosphorylation. In addition, CuONPs exposure aggravated the development of asthma. We conclude that CuONPs exposure has a potential toxicity in humans with respiratory disease.